Training And Mentoring for NU Women Farmers' Group (Kwt) In Increasing Community Creativity Based on Local Resources in Jatidatar Village Bandar Mataram Central Lampung - Habib Ismail; Irfan Nur Muslim; Ghina Valenia Nabilah; Alvitriani Alvitriani; Ahmad Robet; Irma Yuliani; Arum Kumala Putri; Mutiara Lutfi Zakia; Risa Azizah; Usman Zakiya Akmal; Fitri Ambarwati; Nilam Miratus Sholikah; Ahmad Muslimin (Jurnal Insan Pengabdian Indonesia, 2024)
The home industry of the residents of Jatidatar village, Bandar Mataram District, Central Lampung Regency, which was built last yearThe business field is making processed cassava chips. Cassava chips are a widely used food ingredient found in Bandar Mataram Regency. One of the preparations that is popular with the public is cassava chips. In Jati Datar village has a cassava chips manufacturing factory which is still traditional both in terms of harvesting,product processing and marketing. However, in this KKS program that will be our focus Carrying this theme is training and assistance in making cassava chips (seblak cassava) in the marketing sector.The aim of the service activity is to find out the criteria for good cassava as a food ingredient, to know the procedures for making cassava chips (seblak cassava).The method used by researchers in assisting cassava chips (Seblak Cassava) is the result of processing cassava products.This product uses methods in Participatory Action Research (PAR). This method was carried out directly with the NU Women's Farmers' Group (KWT) in Jatidatar Village and the companions also actively followed and practiced this method with the NU Women's Farmers' Group (KWT) in Jatidatar Village. The results obtained from this activity increase the partners' knowledge and skills in processing cassava into cassava seblak Cassava chips products.The benefit of making cassava chips is to increase people's creativity in processing cassava. Previously cassava was only processed into cassava and sold, but now it can be processed into seblak cassava or what is usually called spicy chips through ideas from the community.